RANCANG BANGUN APLIKASI RESEP MASAKAN BERBASIS ANDROID - Supriyanto Supriyanto (Jurnal informasi dan komputer, 2019)
The development of technology and information is increasingly fast now, especially for information. As a product of the development of science and technology, computers are often used both as research tools and as data processing and system development tools. The System Development Method used by researchers in this study is the method of developing the Prototype system with the use case concept. Use case is a description of a system behavior in response to an action / request from outside the system The researcher designed a mobile / android based recipe information system. the search process for recipes is no longer using recipe books or the like because they already use an application in an android smartphone